Integrated surgical and nutritional strategy with gastrostomy for semisolid enteral formula improves postoperative functional recovery after total pharyngolaryngectomy - Ueno, Shuhei; Ogawa, Ryo; Hayakawa, Shunsuke; Matoba, Takuma; Kawakita, Daisuke; Sagawa, Hiroyuki; Iwasaki, Shinichi; Takiguchi, Shuji (International Surgery Journal, 2025)
Background: Enteral nutrition (EN) is commonly administered after total pharyngolaryngectomy. However, it is frequently accompanied by gastrointestinal symptoms, which makes postoperative nutritional management difficult. To address this problem, we developed a surgical strategy using intraoperative gastrostomy for semisolid EN to improve postoperative recovery. Methods: We retrospectively reviewed 41 patients who underwent total pharyngolaryngectomy with free jejunal reconstruction between 2017 and 2022. Twenty-one patients received liquid EN via a nasogastric tube (Group L), and 20 patients received semisolid EN via gastrostomy (Group SS). Postoperative energy intake, weight loss, and changes in prognostic nutritional index (PNI) and psoas muscle index (PMI) were compared between the groups. Results: Group SS achieved significantly higher total energy intake (11,355 vs. 9,800 kcal, p=0.011) and showed lower postoperative weight loss at 1 month (-3.2% vs. -6.5%, p=0.038). At 12 months, Group SS demonstrated superior weight maintenance and better preservation of PNI (46 vs. 41, p=0.04) and PMI (p<0.001 at 6 months). Gastrointestinal symptoms were reduced, and the shortened administration time of semisolid EN enabled earlier mobilization. Conclusions: A surgical approach combining intraoperative gastrostomy with semisolid EN reduced gastrointestinal complications, improved nutritional intake, and preserved muscle mass compared with conventional liquid EN. This integrated perioperative strategy may enhance postoperative recovery and long-term nutritional maintenance in patients undergoing total pharyngolaryngectomy.